Perbandingan Kinerja Keuangan Bank Syariah dan Bank Konvensional dalam Era Digitalisasi Perbankan - Febria Ningsih (Worksheet : Jurnal Akuntansi, 2026)
This study aims to determine the differences in financial performance between Islamic banks and conventional banks in the era of banking digitalization during the period 2017–2023. This study uses quantitative methods with secondary data obtained from the annual financial reports of Islamic banks and conventional banks in Indonesia. Financial performance is measured through the Return on Assets (ROA), Return on Equity (ROE), Non-Performing Loan/Financing (NPL/NPF), Loan to Deposit Ratio/Financing to Deposit Ratio (LDR/FDR), and Operating Expenses to Operating Income (BOPO). Data analysis was performed using descriptive statistics and the Mann-Whitney U test using statistical software. The results show that not all financial performance indicators show differences between Islamic banks and conventional banks. Significant differences were found only in the ROE, NPL/NPF, and BOPO ratios, while the ROA and LDR/FDR ratios showed relatively similar results. These findings suggest that banking digitalization has a greater impact on operational efficiency, financing quality, and capital management than on banks' ability to generate returns from assets. This research is expected to assist banking management and regulators in developing more appropriate strategies and policies to address the development of digital banking.